Adipose Tissue, Diabetes and Chagas Disease - Tanowitz, Herbert B. (2011)
Adipose tissue is the largest endocrine organ in the body and is composed primarily of adipocytes (fat cells) but also contains fibro-blasts, endothelial cells, smooth muscle cells, macrophages and lymphocytes. Adipose tissue and the adipocyte are important in the regulation of energy metabolism and of the immune response. Adipocytes also synthesize adipokines such as adiponectin which is important in the regulation of insulin sensitivity and inflammation. Infection of mice with Trypanosoma cruzi results in an upregulation of inflammation in adipose tissue that begins during the acute phase of infection and persists into the chronic phase. The adipocyte is both a target of infection and a reservoir for the parasite during the chronic phase from which recrudescence of the infection may occur during periods of immunosuppression.